Disastrous Theology and Its Contribution in Encountering Covid-19 Pandemic - Abigail Annie Hutapea (GoAcademica Research & Publishing, 2021)
In confronting a fast, vast and rapid growing and spreading of Covid-19 pandemic in all over Indonesia, it is needed to have a serious concern from every facilitator in this nation, including Christian Religious Education and The Churches of God. Especially, since this pandemic has brought a tremendous impact for social-economic life that has direct connection with welfare and harmony of both family and society life. Christian education and churches, where both of them are inseparable unison, in the end should be able in implementing Disastrous theology which is rooted from the Bible to encounter Covid-19 as the representation of the presence of Jesus in this world.